Household wealth in Latin America - Florencia Torche; Seymour Spilerman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper provides a descriptive analysis of wealth ownership and wealth inequality in Latin American countries, using diverse published sources and primary data analysis for 16 nations. We produce estimates of the distribution of home ownership, land, and financial assets, and find very high wealth concentration in all these types of assets, with the partial exception home ownership. The relevance of informal assets and the historical patterns of wealth accumulation and concentration since colonial times are discussed. Mechanisms of intergenerational wealth transmission are analyzed for the Chilean case.
Keywords: D3; O54; 330; wealth distribution; income distribution; Latin America; home ownership; informal sector; intergenerational transfers; Vermögensverteilung; Privater Haushalt; Grundbesitz; Kapitalanlage; Lateinamerika